The critical factors for permeability-formation factor relation in reservoir rocks: Pore-throat ratio, tortuosity and connectivity. (1st December 2019) - Cai, Jianchao; Zhang, Zhien; Wei, Wei; Guo, Dongming; Li, Shuai; Zhao, Peiqiang
Abstract: The hydraulic properties of reservoir rocks have a directly impact on the flow path of exchange fluid in geothermal and oil reservoir systems. Estimation of hydraulic properties by means of electrical measurement is convenient and nondestructive in these reservoir systems. The mechanism beneath which the pore structure affects electrical and hydraulic flow in porous media is not yet fully understood. In this study, we present a new permeability-formation factor relation based on pore-throat size model and fractal geometry theory. Furthermore, an updated model accounting for the effect of tortuosity and connectivity is applied to characterize the permeability of porous media. The experimental results show that the pore-throat ratio cannot fully describe the relationship between the permeability and the formation factor without considering tortuosity and connectivity. The combined model including pore-throat ratio, tortuosity and connectivity is further proposed to exactly estimate the influence of complex pore structure on the transport behavior associated with electrical parameters. The result also indicates that pore-throat ratio, tortuosity, and connectivity are the three key factors determining hydraulic properties in porous media. This means the estimation of electrical conductivity changes with permeability that depends on accurate characteristic of micro-structural properties of reservoir rocks. Highlights: A relationship between hydraulic property and electrical conductivity is proposed. The pore-throat structure is variable based on fractal scaling in the model. Prediction of the model matches the regular order of magnitude of permeability. The tortuosity and connectivity influences on permeability are presented.